The Marketing Strategy of Nike is Analyzed from STP and SWOT - Xu, Xiaochun (Transactions on Social Science, Education and Humanities Research, 2024)
At present, the sports brand industry is becoming increasingly popular, and more and more brands and the industry competition is becoming more and more fierce. Nike, as an industry giant, has great reference value for studying the marketing strategy of sports brands. Based on STP and SWOT analysis, the rise and future development of Nike are analyzed. The results from STP found that Nike’s accurate positioning of the target market has provided a great help for their marketing methods in the market. While studying SWOT, the results found that they attract consumers with unique design concepts and superb manufacturing processes. At the same time, there are hidden dangers of fierce competition in the industry. Finally, for Nike’s marketing, there are some suggestions for its future development. Nike as a leader in the sports brand industry, with reference to its marketing strategy and means, helps to cultivate marketing thinking and training management skills.